Health Belief Model in The Prevention of Type-2 Diabetes Mellitus in Fertile Age Couple - Achmad Lukman Hakim; Agustina Sari (Jurnal Kesehatan Masyarakat, 2025)
Sufferers with diabetes want to well recognize the threat of diabetic headaches and the shape of the Health Belief Model (HBM) with recognize to constructs suitable for intervention. This study aims to determine the effect of the health belief model on the prevention of type 2 diabetes mellitus in fertile age couple. The research design was cross sectional. The research sample was fertile age couple who are in the area of Depok City, West Java as many as 399 respondents. Data analysis used a structural equation modeling approach with the partial least squares method. The results showed that there was a perceived effect on the prevention of type-2 diabetes mellitus with a t-statistic of 13.331880, there was an effect of self-efficacy on the prevention of type-2 diabetes mellitus with a t-statistic of 2.221879, there was an effect of cues to action on the prevention of type-2 diabetes mellitus with a t-statistic of 2.482949, and the perceived indicator that has the most influence on the prevention of type-2 diabetes mellitus was barriers with a t-statistic of 180.528565. Based on the value of R2, the magnitude of the effect of perceived, self-efficacy, and cues to action on the prevention of type-2 diabetes mellitus was 89.52%. From the Q2 value, the model in this study has a relevant predictive value, where the model used can explain the information contained in the research data by 89.52%. There was an effect of health belief model on the prevention of type 2 diabetes mellitus in fertile age couple. Another dominant variable that influences the prevention of type 2 diabetes mellitus in fertile age couple was perceived and on indicators of barriers.